FRASE PREPOSISI BAHASA INDONESIA: ANALISIS X BAR - Mulyadi Mulyadi Mulyadi (KAJIAN SASTRA, 2010)
As an aglutinating language, Indonesian is rich of morphological markers, such as afixes and prepositions. However, from the X-bar perspective, the syntactic behaviour of these markers in forming prepositional phrases has not been clearly depicted. This paper aims to describe the internal structure of prepositional phrase (PP) in Indonesian.  This study used written data taken from various sources. The result of the analysis shows that PP is composed of a complement (Comp), a modifier (Mod), and a specifier (Spec). The rules of forming PP cover : (1) PP = P’, Spec;  P’ = P’, Comp, (2) PP = P’, Spec; P’ = P’, Mod.; P’ = P, Comp, (3) FP = P’, Spec; FP = P’, Spec; P’ = P, Mod.; Y= P, Comp. Key words: prepositional phrases, phrase structure, X‑bar theory http://ejournal.undip.ac.id/index.php/kajiansastra/editor/submission/2671